Hubungan Antara Kepuasan Berhuni dan Sikap Terhadap Tempat - Andina Syafrina; Angela Christysonia Tampubolon; Nunik Hasriyanti; Hanson Endra Kusuma (Tesa Arsitektur, 2019)
The quality of the housing must be properly considered in order to function properly. Currently many housing development failures because lack of attention to quality aspects. The number of failures because lack of knowledge on occupant satisfaction aspects. The residential satisfaction is one of the factor that formers the attitudes toward the place which is the result of interaction between human and the environment where they live and contribute to improvement the quality of life. The aim of this study was to find out the dimension of residential satisfaction in the housing environment, the dimension of attitude toward the place, and the relation between public satisfaction and attitude toward the place. Data collection was carried out based on survey using an online questionnaire. The results showed five dimensions of residential satisfaction in the housing environment, namely environmental comfort, environmental facilities, green open space, environmental management, and infrastructure. There are also two dimensions of attitude toward the place, namely participation and adjustment. The result also showed the tendency of the satisfaction dimension to the environmental comfort related to the attitude of participation and adjustment.